The Cultural Adoption of Human Rights in a Local Context: A Case in Norway - Taj, Farhat (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2020)
Growing ethnic and cultural diversity in welfare states like Norway has created a gap between the legal rights and the social realities of vulnerable individuals in certain immigrant communities. Such growing diversity calls for innovative approaches to ensure the enjoyment of individual rights without generating unnecessary controversies regarding the cultural legitimacy of human rights. Combining legal literacy with vernacularisation strategies for the cultural adoption of human rights is an effective approach to promote and protect human rights in situations where individual rights seemingly clash with the authoritative interpretation of cultural norms and values. This article illustrates the said approach using a polygamy case in Norway handled by Pakwom, an Oslo-based immigrant-women’s non-governmental organisation.